The Role of "Bone Immunological Niche" for a New Pathogenetic Paradigm of Osteoporosis. (30th September 2015) - Pagliari, Danilo; Ciro Tamburrelli, Francesco; Zirio, Gianfranco; Newton, Estelle E.; Cianci, Rossella
Abstract : Osteoporosis is characterized by low bone mass and microarchitectural deterioration of bone tissue. The etiology and pathogenetic mechanisms of osteoporosis have not been clearly elucidated. Osteoporosis is linked to bone resorption by the activation of the osteoclastogenic process. The breakdown of homeostasis among pro- and antiosteoclastogenic cells causes unbalanced bone remodeling. The complex interactions among these cells in the bone microenvironment involve several mediators and proinflammatory pathways. Thus, we may consider the bone microenvironment as a complex system in which local and systemic immunity are regulated and we propose to consider it as an "immunological niche." The study of the "bone immunological niche" will permit a better understanding of the complex cell trafficking which regulates bone resorption and disease. The goal of a perfect therapy for osteoporosis would be to potentiate good cells and block the bad ones. In this scenario, additional factors may take part in helping or hindering the proosteoblastogenic factors. Several proosteoblastogenic and antiosteoclastogenic agents have already been identified and some have been developed and commercialized as biological therapies for osteoporosis. Targeting the cellular network of the "bone immunological niche" may represent a successful strategy to better understand and treat osteoporosis and its complications.